Improvement of a mobile vacuum evaporator for the production of multicomponent vegetable semi-finished products with adjustable thickening for new product formulations - Chuiko, Lyudmila; Tytarenko, Nataliia; Milenin, Andrii; Chmil, Hanna; Sabadash, Sergei; Ibaiev, Eldar (Technology audit and production reserves, 2025)
The object of research is the process of manufacturing multicomponent vegetable semi-finished products with adjustable thickening of the mass from Jerusalem artichoke, carrot and pumpkin on an improved mobile vacuum evaporator. Traditional evaporators are characterized by high energy and metal consumption, the presence of a steam jacket with complex temperature range regulation, which leads to an increase in the cycle duration and losses of natural ingredients. The lack of mobility of traditional equipment does not allow it to be used in mobile lines of agricultural complexes and craft production, which is relevant for decentralized use of the device, for example, in front-line regions. In the course of improving the mobile vacuum evaporator, classical methods were used to analyze heat and mass transfer, determine the content and degree of preservation of useful natural ingredients in the conditions of mobile production of multicomponent semi-finished products with adjustable thickening. The design improvement is based on the use of a film-like electric heater of the radiant type, additional increase in the useful heat exchange surface due to the use of a mixer with a heating circuit and Peltier elements for secondary air recovery. Such actions contributed to increasing the resource efficiency of the technological cycle and stabilizing the temperature effect during the controlled thickening of natural masses. The duration of controlled thickening of multicomponent masses was reduced by 37%, the specific heat consumption by 15.5%, the loss of vitamin C by 21%, the preservation of inulin (94%), β-carotene (87%) and 88% preservation of polyphenols. It is the introduction of electric heating of the working chamber of the apparatus and the artificial increase in the useful heat exchange surface actually due to the mixer circuit, which is heated by 27%, which contributes to the stabilization of the temperature field. And the use of an air thermal insulation jacket allows for the recovery of secondary warm air, further increasing the resource efficiency of the technological cycle. The improvement of the apparatus contributes to the resource-saving processing of plant raw materials into polycomponent semi-finished products of high readiness with adjustable thickening, in particular within 25–45% of dry matter for further introduction into the formulations of new products. A polycomponent semi-finished product of high readiness with adjustable thickening can be used in functional drinks, baby food, confectionery fillings and meat and vegetable products. A comparison of the improved design with basic evaporators is characterized by resource efficiency, mobility for agricultural sectors in conditions of decentralized processing, for example in front-line regions.